Green synthesis of novel coumarin derivatives via grinding approach and their antimicrobial evaluation - Anhar Abdel-Aziem (Green Chemistry Letters and Reviews)
Herein, a rapid, clean, less expensive and environmentally friendly route to a novel series of coumarins bearing thiazoles or 1,3,4-thiadiazoles was developed via grinding method under solvent conditions. Thus, 6-bromo-3-(2-bromoacetyl)-2-chromen-2-one was treated with cyanothioacetamide to produce thiazole-2-acetonitrile derivative 2, which was then transformed to iminocoumarins by reacting with hydroxyaldehydes. Hydrolysis of iminocoumarins by conc. HCl furnished coumarins. Furthermore, treatment of compound 2 with phenylisothiocyanate produced thioanilide which interacts with hydrazonoyl chloride and/or α-halocarbonyl compounds afforded 1,3,4-thiadiazole and thiophene derivatives, consequently. All the newly prepared coumarins were screened against six pathogenic microorganisms. The results indicated that compounds 7 and 12 were the most effective against Bacillus pumilis, while compound 4b was highly active against Streptococcus faecalis. Also, compound 5b was highly active against Enterobacter cloacae. Compounds 2 and 7 were higher active compared with reference drug ketoconazole against fungi Saccharomyces cerevisiae.